The effectiveness of paint remover to resin adhesive residue on base mesh of metal bracket - Abubakar, Sukarto; Thahar, Bergman; Hambali, Tono S.; Salim, Jono (Padjadjaran Journal of Dentistry, 2008)
The purpose of this study is to know whether paint remover can be used to remove resin adhesive residue on the base mesh of metal bracket. The study is based on in vitro experiment with descriptive-comparative and the test sample is 30 used brackets after treatment at Orthodontic Specialist Clinic Faculty of Dentistry Universitas Padjadjaran. The sample is randomly divided into 3 groups and each group consists of 10 brackets and then its bath in paint remover for 8, 10, and 12 hours, respectively and statistically analyzed with chi-square (χ2) and α= 0.05 and the results show signifi cantly diff erence between resin residue before and after immersion, while resin residue after immersion its group showed there are no signifi cant diff erences. Based on analyzed, it can be concluded that paint remover can be used to remove resin adhesive residue on base mesh of metal bracket and that 8, 10, and 12 hours immersion duration the result show effectiveness similiary.